CYCLIC LABILITY OF HOMEOSTASIS IN GILTS - Usenko, S. O. (Scientific Progress & Innovations, 2019)
Hormonal regulation of the body plays an important role in the formation of homeostasis and condition-ing the implementation of the hereditary program during the individual development of the animal. There-fore, in recent years, the number of studies on the problems of animals’ endocrine system formation and the participation of hormones in the processes of ontogenesis has especially increased. The purpose of the re-search was to determine the peculiarities of homeostasis formation in gilts depending on the phases of the reproductive cycle. Clinically healthy gilts of Myrhorodska pig breed at different phases of the reproduction cycle: luteal phase, estrus, and on the 15th, 20th, 30th, 60th, 90th, 104th, 113th days of pregnancy and 12 hours after farrowing, were used in the experiment. The levels of thyroxin, triiodothyronine, estradiol-17β, progesterone and testosterone were determined in the blood serum. The state of prooxidant-antioxidant ho-meostasis in the blood was researched for the activity of: superoxide dismutase, catalase, xanthine oxidase; concentrations of: diene conjugates, TBA-active compounds, reduced glutathione, ascorbic and dehy-droascorbic acids, vitamin A and vitamin E. It was found out that the amount of steroid hormones in the blood of gilts is labile and due to the physiological state, namely during the estrus, relative to the luteal phase the levels of thyroxin, triiodothyronine, estradiol-17β and testosterone increased, and progesterone decreased. Such changes are accompanied by accelerating the processes of peroxide oxidation: xanthine oxidase activity increases (p<0.05), the content of diene conjugates (p<0.05) and TBA-active compounds are increased by1.3 times. During the two months of pregnancy, the total concentration of thyroid and steroid hormones increases. Such metabolic shifts cause a decrease in the intensity of peroxidation processes. Be-fore farrowing there was a decrease in the levels of thyroxin, triiodothyronine and progesterone. The intensi-fication of peroxidation was determined by: the increase of CSR activity (p<0.05) and SOD (p<0.01), the content of dehydroascorbic acid, diene conjugates (p<0.05) and TBA-active complexes, as well as the de-crease of the concentration of reduced glutathione (p<0.01) and vitamin E. It was found out that after far-rowing, the serum thyroxin concentration increased and the progesterone, testosterone and estradiol-17β decreased. There was the decrease in the intensity of lipid peroxidation: the decrease in the content of DC in 2.5 and TBA-active complexes by 1.5 times, against the background of decreasing the amount of vitamin A and vitamin E by 11 %. The found features of cyclic homeostasis lability in gilts’ blood are determined by the phases of the reproductive cycle.